Orthopedic implant infections: Incompetence of Staphylococcus epidermidis, Staphylococcus lugdunensis, and Enterococcus faecalis to invade osteoblasts. Issue 3 (30th December 2015) - Campoccia, Davide; Testoni, Francesca; Ravaioli, Stefano; Cangini, Ilaria; Maso, Alessandra; Speziale, Pietro; Montanaro, Lucio; Visai, Livia; Arciola, Carla Renata
Abstract: Septic failure is still the major complication of prosthetic implants. Entering host cells, bacteria hide from host immune defenses, shelter from extracellular antibiotics, and cause chronic infection. Staphylococcus aureus, the leading etiologic agent of orthopedic implant infections, is able to enter bone cells and induce osteoblast apoptosis, osteoclast recruitment, and highly destructive osteomyelitis. Staphylococcus epidermidis, Staphylococcus lugdunensis, and Enterococcus faecalis are opportunistic pathogens causative of implant‐related infections. This study investigated the ability to internalize into osteoblastic MG63 cells of 22 S. epidermidis, 9 S. lugdunensis, and 21 E. faecalis clinical isolates from orthopedic implant infections. Isolates were categorized in clusters by ribotyping. Internalization assay was carried out by means of a microtiter plate‐based method. S. epidermidis, S. lugdunensis, and E. faecalis strains turned out incompetent to enter osteoblasts, exhibiting negligible internalization into MG63 cells, nearly three orders of magnitude lower than that of S. aureus . Osteoblast invasion does not appear as a pathogenetic mechanism utilized by S. epidermidis, S. lugdunensis, or E. faecalis for infecting orthopedic implants. Moreover, it can be inferred that intracellularly active antimicrobials should not be necessary against implant infections caused by the three bacterial species. Finally, implications with the uptake of biomaterial microparticles by nonphagocytic cells are enlightened. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 788–801, 2016.